Effect of Central Bank Digital Currencies (CBDCs) on the Global Financial System's Stability in Kenya - Maina, Timothy (International Journal of Finance, 2025)
Purpose: The purpose of this article was to analyze effect of central bank digital currencies (CBDCs) on the global financial system's stability in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The introduction of central bank digital currencies (CBDCs) in Kenya could enhance financial inclusion and reduce transaction costs, particularly for the unbanked. However, risks such as cybersecurity threats, financial disintermediation, and impacts on traditional banking systems exist. CBDCs could also give central banks more control over monetary policy. While offering benefits, their success depends on strong regulatory frameworks, technological infrastructure, and addressing privacy concerns. Careful implementation and international coordination are essential for ensuring financial stability in Kenya's ecosystem. Unique Contribution to Theory, Practice and Policy: Financial intermediation theory, theoretical framework of financial stability & network effects theory may be used to anchor future studies on the effect of central bank digital currencies (CBDCs) on the global financial system's stability in Kenya. Central banks should adopt a cautious and incremental approach to CBDC implementation, as recommended. Governments and central banks worldwide must engage in international dialogues to ensure coordinated approaches to CBDC adoption.